Role of Stock Performance as an Intervening Variable in a Relationship Between Profitability, Leverage, Growth and Company Value - Hendy Tannady; Nuzulya Pahlawi; Moch Arif Hernawan; Deddy Novie Citra Arta; Sri Dewi Yusuf (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The reason of this observe is to analyze and decide the effect of profitability, leverage, and growth on the performance of property sector company shares, to analyze and determine the effect of profitability, leverage, growth and stock performance on the company value of property sector companies and to analyze and determine the effect of profitability, leverage, and growth on company value with stock performance as an intervening variable for property sector companies listed on the IDX in 2017-2021. This research is protected in quantitative research the usage of secondary facts. This research is a quantitative research conducted to see the effect of profitability, leverage, growth on company value with stock performance as an intervening variable with case studies on businesses within the belongings, actual estate and constructing creation sectors indexed at the IDX in 2017-2021. In this study the authors used secondary statistics from annual reviews and financial reports. This study concludes that there is no effect of profitability on stock performance, there is an effect of profitability on firm value, there is an effect of leverage on stock performance, there is an effect of leverage on firm value, there is an effect of growth on stock performance, there is an effect of growth on firm value, there is an effect on performance stock on firm value, on firm value with stock performance as an intervening variable, there is an influence between growth on firm value and stock performance as an intervening variable.